"Good Types" in Authoritarian Elections: The Selectoral Connection in Chinese Local Congresses. (March 2017) - Manion, Melanie
A new electoral design for subnational congress elections in China allows me to investigate the informational utility of authoritarian elections. Authoritarian regimes are notoriously bad at solving the moral hazard problem in the voter's agency relationship with politicians. Borrowing from the literature on political selection, I theorize that authoritarian elections can nonetheless solve the adverse selection problem: Chinese voters can use their electoral power to select "good types, " with personal qualities that signal they will reliably represent local interests. I analyze original data from a survey of 4, 071 Chinese local congressmen and women, including voter nominees and communist party nominees. I find that voters do in fact overcome coordination difficulties to nominate and elect "good types." In contacting politicians about local problems after the elections, however, voters hedge their bets by contacting regime insiders too. At these very local levels, congressional representation by means of political selection co-exists with communist party nominating and veto power in the electoral process.